Case Report: Identification of novel CDH2 mutation (p. P183A het)-induced arrhythmogenic cardiomyopathy in China - Kun Li; Yifei Wang; Jing Yang; Fang Liu; Fulan Liu; Ping Zhang (Frontiers in Cardiovascular Medicine, 2023)
BackgroundArrhythmogenic cardiomyopathy/dysplasia (ACM) is an inheritable heart disease closely related to gene variations induced heart fibrofatty replacement, which increases the risk of arrhythmia events and even sudden cardiac death. In this study, we reported a 10-year-old patient with a novel mutation diagnosed with ACM.Case presentationWe present the case of a 10-year-old patient admitted with recurrent palpitation, whose electrocardiogram suggested the existence of right ventricle origin premature ventricular contractions and ε wave. Furthermore, echocardiography showed an enlarged right ventricle corrected to a body surface area of 29.57 mm/m2. The diagnosis of ACM was clear. Further gene sequencing revealed a novel heterozygous missense mutation of CDH2 (cadherin-2) c.547C > G (p. P183A) that potentially increases ACM risk by affecting adherens junctions of the intercalated discs.ConclusionsThis is the first case of CDH2 mutation (c.547C > G, p. P183A) related ACM in the Chinese population. Compared to previously reported mutations inducing ACM by affecting desmosome function, the newly reported CDH2 variation revealed a novel potential mechanism that induces ACM by disturbing cell-cell adhesion.